Lecturer's Behavior Finance in Making Investment Decisions on Financial Assets from The Perspective of Psychological Factors - Yuniningsih - Yuniningsih; Bowo Santoso; Nanda Farah Zhafirah; Difa Rachmayanti; Dina Anggraini (LPPM of NAROTAMA UNIVERSITY, 2022)
This research is a continuation of research year 1 with the title “Lecturer Financial Asset Investment Interest in Surabaya”. In the first year of research, the research was limited to investment interest as an endogenous latent variable. 3 exogenous latent variables were consisting of financial literacy, attitude, and motivation. There is also 1 moderating variable, namely family. The purpose of this study was to determine the behavior of lecturers in Surabaya in making investment decisions. 3 factors as exogenous variables are investment interest, risk perception, and risk tolerance. These factors affect investment decisions as endogenous variables. The analysis tool used is SEM PLS and with 56 participant’s data. The results show that investment interest greatly influences investment decisions. while the other two variables, risk perception, and risk tolerance do not affect investment decisions. The dependent variable or as an endogenous variable in this study is investment decisions and 3 exogenous latent variables, namely investment interest, risk perception, and risk tolerance.